Immobilization and Stabilization of Enzyme in Biomineralized Calcium Carbonate Microspheres - Lee, Chan Hee; Jin, Eon Seon; Lee, Jin Hyung; Hwang, Ee Taek (Frontiers in Bioengineering and Biotechnology, 2020)
Biomineralized uniform and well-organized calcium carbonate microspheres were synthesized for enzyme immobilization, and the immobilized enzyme was successfully stabilized. The physicochemical parameters of calcium carbonate were studied using scanning electron microscopy with energy-dispersive X-ray spectroscopy, particle size analysis, X-ray diffraction analysis, Fourier-transform infrared spectroscopy, and surface area measurement. Additionally, Barrett-Joyner-Halenda adsorption/desorption analysis showed that the calcium carbonate microspheres provided efficient mesopore space for enzyme loading. As a model enzyme, carboxyl esterase was entrapped and then cross-linked to form an enzyme structure. In this aggregate, the cross-linked enzymes cannot leach out from mesopores, resulting in enzyme stability. The hydrolytic activities of the free and cross-linked enzymes were analyzed over broad temperature and pH ranges. The cross-linked enzyme displayed better activity than the free enzyme. Furthermore, the immobilized carboxyl esterase was found to be stable for more than 30 days, preserving 60% of its initial activity even after being reused more than 10 times. This report is expected to be the first demonstration of a stabilized cross-linked enzyme system in calcium carbonate microspheres, which can be applied in enzyme catalyzed reactions involved in bioprocessing, bioremediation, and bioconversion.